Identification and Comparison of Colletotrichum Secreted Effector Candidates Reveal Two Independent Lineages Pathogenic to Soybean - Thaís R. Boufleur (MDPI AG, 2021)
Colletotrichum is one of the most important plant pathogenic genus of fungi due to its scientific and economic impact. A wide range of hosts can be infected by Colletotrichum spp., which causes losses in crops of major importance worldwide, such as soybean. Soybean anthracnose is mainly caused by C. truncatum, but other species have been identified at an increasing rate during the last decade, becoming one of the most important limiting factors to soybean production in several regions. To gain a better understanding of the evolutionary origin of soybean anthracnose, we compared the repertoire of effector candidates of four Colletotrichum species pathogenic to soybean and eight species not pathogenic. Our results show that the four species infecting soybean belong to two lineages and do not share any effector candidates. These results strongly suggest that two Colletotrichum lineages have acquired the capability to infect soybean independently. This study also provides, for each lineage, a set of candidate effectors encoding genes that may have important roles in pathogenicity towards soybean offering a new resource useful for further research on soybean anthracnose management.